Potensi Bahaya Pada Area Kerja Pelabuhan - Muhammad Fachri Ridwan; Faiz Hamdi; Tivany Edwin (Jurnal Serambi Engineering, 2024)
Port work areas are prone to potential hazards. This study aims to identify hazards and assess risks in the port work area, especially in the operational process of loading and unloading containers using the HIRADC method at five port work area locations in Padang City. The results show that there were 15 medium risk, 13 high risk observed. There is high risk of accidents in liquid bulk, dry bulk and container activity locations such as being crushed by containers, being hit in the container area, dust/noise and sea air pollution due to the process of loading/unloading liquid bulk and dry bulk area. The medium risk levels consist of being hit by lift transport, CO2 gas fumes and being crushed by material transport. To reduce and eliminate potential hazards, risk management is required by identifying and analysing potential hazards, assessing risks and recommending controls, one of which is the Hazard Identification Risk Assessment and Determining Control (HIRADC) method. Recommended controls include preparation of marine pollution control equipment (oil booms), operational maintenance of loading and unloading equipment, installation of signs indicating low to high hazard areas, provision of light fire extinguishers, administrative controls and use of personal protective equipment (PPE).